2014
DOI: 10.1039/c4ta01171f
|View full text |Cite
|
Sign up to set email alerts
|

In situ coating of NiO on Ni-silicide nanowires with roughened surfaces for improved electrochemical energy storage

Abstract: NiO layers were coated in situ onto Ni-silicide nanowires by an oxidation in air. The surface of the nanowires had been previously roughened by etching in HF solution. It is found that the roughened surface is very helpful to enhance the in situ coating ability of NiO on the nanowires. When the resulting samples were used as anodes for lithium-ion batteries, a high reversible capacity of 1.28 mA h cm À2 was obtained for the surface-roughened nanowires with 30 min HF-treatment, which is 3 times higher than that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…More recently, core-shell nanostructures with conductive matrices have been realized to be an effective approach to address the above-mentioned issues, in which the core functions as a built-in current collector to accommodate the enormous volume change and facilitate the electron collection and transport [29][30][31][32][33][34]. For instance, Huang et al reported Ni micro-nanocone hierarchical electrodes by economical electrodeposition method with a crystallization modifying agent, which showed outstanding Li storage properties with reversible capacity over 800 mAh g -1 after 100 th cycle [35].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, core-shell nanostructures with conductive matrices have been realized to be an effective approach to address the above-mentioned issues, in which the core functions as a built-in current collector to accommodate the enormous volume change and facilitate the electron collection and transport [29][30][31][32][33][34]. For instance, Huang et al reported Ni micro-nanocone hierarchical electrodes by economical electrodeposition method with a crystallization modifying agent, which showed outstanding Li storage properties with reversible capacity over 800 mAh g -1 after 100 th cycle [35].…”
Section: Introductionmentioning
confidence: 99%
“…NiSiNWs are explored as an active anode material; these NWs are attractive due to their potential for high-capacity and good rate capability, as well as their low-temperature growth in the presence of Ni and Si precursors (~450 °C) 20 . NiSi has a gravimetric capacity of ~1300 mAh g −1 , 21 23 which is lower than that of Si but still much higher than graphite. An additional advantage of NiSi is related to its metallic conduction, with a typical resistivity of ~10 μΩ cm for single crystals 24 .…”
Section: Resultsmentioning
confidence: 97%